PEMBERDAYAAN USAHA MIKRO KECIL DAN MENENGAH (UMKM) MELALUI PROGRAM BINAAN DI PROVINSI BALI - Ni Nyoman Sunariani; A A N Oka Suryadinatha Gorda; Ida IDM Rai Mahaputra (Jurnal Ilmiah Manajemen & Bisnis, 2017)
ABSTRACTUMKM in national economy play an important role and strategic for the economic growth, not only in developing countries like Indonesia but also in developed countries. Nine district of a city that has the potential strategic support revenue in the area.Local revenue Bali Province to decrease from year 2015 it is only of 41,29 %, is much lower compared to last 2014 of 60,92 %. Which is due by UMKM sector.This condition is making UMKM very reasonable and potentially more empowered.In 2010, especially UMKM sector experienced a decline in the value exsport from year to year, declined significantly. From research exploratif to the field , problems identification , with AHP ( analitical hierarchy process ) found way UMKM, in Bali Province , who improve significantly sales good for the domestic market and exports Bali Province .This empowerment , in acceleration regional economic growth , job creation and the increase in competitiveness UMKM products .The research results show factors barrier UMKM, namely capital , human resources , access banking , of the nature of products lifetime short , and the limited market access good in the market national and international .Program under the jurisdiction of UMKM in Bali Province be done in collaborate with the government , banking , soe , cooperatives , lpd , bumd , college collaborated through an incubator business .Based on the research done , can formulated policy recommendations , under the jurisdiction of program partner between the government and UMKM in Bali Province. The government needs to simplification licensing procedure, cheap and fast through one roof.